A sixty-year timeline of the Air Force Maui Optical and Supercomputing Site - Clifford, Megan; Baiocchi, Dave; Welser, William, IV (Research report (Rand Corporation), 2013)
This document contains a timeline of key events in the history of the Air Force Maui Optical and Supercomputing Site (AMOS). AMOS is located on the island of Maui, Hawaii, and is comprised of two physically separate facilities: the Maui Space Surveillance Complex (MSSC) located on the top of the Haleakala volcano and the Maui High Performance Computing Center (MHPCC) located in Kihei. MSSC was first imagined as an optical research observatory in the early 1950s. Since then, the site's mission, management structure, and operational partners have changed several times to accommodate the contemporary challenges and research tools. This timeline documents some of these historical changes. The events contained in this document focus primarily on the MSSC, but MHPCC has always maintained a strong collaboration with the MSSC, so several events associated with MHPCC are included. The timeline is provided in both tabular and printable wall chart formats.